PENGARUH ROTASI. KERJA. TERHADAP. KINERJA. PEGAWAI STRUKTURAL DI RSUD CIAWI - Sutrisna, Indra; S Zenju, Nandang; Pratidina, Ginung (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2018)
This study aims to determine the effect of work rotation on employee performance RSUD Ciawi. The method used is the method of associative research, data collection in the form of observation, interview, and questionnaire. Sampling technique used in this research is Probability Sampling technique that is Simple Random Sampling. The correlation used in this study is Rank Spearman correlation, with the number of samples of 55 (fifty five) people. The results showed that the correlation between work rotation variables and employee performance variable was 0.490 in medium relations category, and significant. Significant means the correlation is significant at the level / level of 1%. In this study work rotation affect performance as much as 24.01%. Suggestions in this study that need to be improved again on the dimension of experience, rotation should be done based on the length of time and work experience, because the experience of employees will affect with the work of employees. And should be in the work rotation more tailored to the background of employees.Â Keywords: Job Rotation, Employee Performance, Structural Employee